Situasi Keluarga Berencana Di Provinsi Kalimantan Timur - Edwardus Iwantri Goma (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2019)
Since the International Conference on Population and Development (ICPD) in Cairo in 1994 there has been a paradigm shift related to the orientation of family planning program services throughout the world. From family planning services which are oriented towards reducing birth rates to prioritizing individual reproductive health by respecting the reproductive rights of each individual. The province of East Kalimantan in a number of demographic and health surveys in Indonesia experienced fluctuations up and down against several family planning indicators that are often used. This phenomenon must certainly be a concern of the government of the Province of East Kalimantan in an effort to achieve the national TFR target of 2.1 in 2025. This paper is aimed at finding out 1) the condition of Family Planning in East Kalimantan Province compared to other Provinces at Kalimantan Island and 2) the condition of family planning in the province of East Kalimantan. This paper uses the literature study method by utilizing data from Indonesian demographic and health survey (IDHS) 2007, 2012, 2017 and other relevant sources. The results of Indonesia's demographic and population survey in 2017 showed that the highest percentage of contraceptive use in Kalimantan island was at West Kalimantan Province and the lowest was at North Kalimantan Province. From the aspect of contraceptive use, the method / type of injectable birth control is the choice most widely used by acceptors at East Kalimantan province. While the results of Indonesia's demographic and health survey in 2017 on the TFR indicator of 2, 7, CPR of 55 percent and Unmed Need of 10, 2 percent. .